Path-Analytic Study of Students’ Home Background, Academic Motivation, Self-Concept on Attitude and Achievement in Senior Secondary School Mathematics in Ogun State, Nigeria (2010)
Mathematics is a fundamental subject which functions as a basic index for understanding and mastery of various aspects of science as well as the complexity of modern technology. Thus, every individual needs some knowledge of mathematics in order to live a useful life and be an effective member of the society. Several studies in the past have focused on the factors associated with students’ poor academic achievement in mathematics. However, very few of those have considered the influence of multiple indicators on students’ achievement in mathematics at the secondary school level with a view to establishing their combined influence on students’ academic achievement. This study, therefore investigated the causal-effects of home background variables, academic motivation and self-concept on students’ attitude and achievements in mathematics among secondary school students in Ogun State, Nigeria. The study employed ex-post facto type of research. The sample was selected using the multi-stage sampling technique. Two thousand four hundred students from 60 selected schools in nine local government areas within Ogun State, Nigeria were involved. Five research instruments namely; Attitude towards Mathematics Questionnaire; (r = 0.73), Self-concept Scale; (r = 0.71), Parents’ Support Scale; (r = 0.66), Academic Motivation Scale; (r = 0.85) and Mathematics Achievement Test; (r = 0.84) were used. Four research questions were answered and data analysed using path analysis technique at .05 level of significance. There were 22 significant and meaningful pathways through which the predictors caused variation in students’ attitude to and achievement in mathematics. Out of the 22 pathways, three were direct while 19 were indirect. The original and the reproduced correlation coefficients were also compared and the discrepancies were found to be minimal. Out of the seven predictor variables hypothesised, only one (i.e, parents’ education), significantly exerted direct influence on achievement. However, all the seven predictor variables significantly exerted direct and indirect influence on students’ attitude thus; academic motivation (β = 0.321); self-concept (β = 0.187); parents’ support (β = 0.105); number of children in the family (β = 0.011); parents’ education (β = 0.007); parents’ occupation (β = 0.005); and age of mother at birth of the child (β = 0.001). Therefore, since home background variables (i.e, age of mother at birth of the child, parents’ education, occupation and support, number of children in the family) as well as academic motivation and self-concept brought about greater improvement in students’ attitude towards mathematics, it is pertinent that parents be encouraged to put on earnest efforts in motivating students towards the learning of mathematics. Such encouragement and support will thus supplement the efforts of the teachers at school and help students cultivate positive attitude towards mathematics. Additionally, since parents’ education influences students’ academic achievement in mathematics, the government and all stakeholders in the education sector should endeavour to implement its policy on basic education for all and thus create an enlightened society in which every parent would be educated enough to have a positive influence on their children especially in their attitude towards mathematics, which would in turn lead to better achievement in the subject.